2021
DOI: 10.3390/ijerph182312540
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal Barriers Hindering Adoption of Telepsychiatry among Mental Healthcare Professionals: Israel as a Case-Study

Abstract: Despite proven advantages for the use of telemedicine in psychiatry, mental healthcare professionals have shown deep-seated mistrust and suspicion of telepsychiatry, which hinders its widespread application. The current study examines the attitudes of Israeli mental health professionals towards telepsychiatry and seeks to uncover the effects of experience and organizational affiliation on its adoption. The methodology included qualitative and thematic analysis of 27 in-depth interviews with Israeli mental heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…A questionnaire was developed, following a thorough literature review, as well as in-depth interviews with Israeli mental healthcare professionals regarding their attitudes toward telepsychiatry. 23 Based on interviewees’ own phrasing, we distilled 30 statements covering the following issues: efficacy, efficiency, quality of treatment, alliance formation, diagnosis, compensation, legality, limitations, and barriers. This questionnaire was first pilot-tested on a small control group, checking for clarity of language and ease of use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire was developed, following a thorough literature review, as well as in-depth interviews with Israeli mental healthcare professionals regarding their attitudes toward telepsychiatry. 23 Based on interviewees’ own phrasing, we distilled 30 statements covering the following issues: efficacy, efficiency, quality of treatment, alliance formation, diagnosis, compensation, legality, limitations, and barriers. This questionnaire was first pilot-tested on a small control group, checking for clarity of language and ease of use.…”
Section: Methodsmentioning
confidence: 99%
“…A previous qualitative study among Israeli mental healthcare professionals found indications that positive attitudes toward telepsychiatry are indeed correlated with levels of experience with this method. 23 Therefore, the purpose of the current study has been to examine longitudinal changes in attitudes toward telepsychiatry throughout the evolution of the COVID-19 pandemic in Israel, and to assess whether distinct sub-groups within the local mental healthcare professionals were more susceptible to such change. Furthermore, the current study sought to elaborate on possible points of consensus among local professionals regarding telepsychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…Our overall findings are in alignment with previous studies of mental health providers’ attitudes toward video consultations. Similarly, the studies found that clinicians believed video consultations could be effective and useful, since it facilitated access and met patient demands, but also that the medium was more impersonal and made it more difficult to detect non-verbal cues ( 10 , 18 ). In general, the studies found that the overall attitudes were largely positive; providers were satisfied and favored the use of videoconferencing; and furthermore, the studies reported that the clinicians found it easy to use ( 10 ).…”
Section: Discussionmentioning
confidence: 96%
“…Traditional inpatient psychotherapy and consultation played a kind of social role -forcing the patient to leave his home, interact with other people and spend time in a stationary conversation with another human being. In a study by Magal et al [63], respondents expressed concern that using video conferencing at home exacerbates patients' social isolation. This is important given the current times, in which many people are struggling with loneliness, compounded by the COVID 19 pandemic.…”
Section: Social Isolationmentioning
confidence: 99%
“…W badaniu Magal i wsp. [63] ankietowani wyrazili zaniepokojenie, że korzystanie z wideokonferencji w domu pogłębia izolację społeczną pacjentów. Jest to ważne ze względu na obecne czasy, w których wiele osób zmaga się z problemem samotności, dodatkowo potęgowanym przez pandemię COVID19.…”
Section: Izolacja Społecznaunclassified